BRITISH IDENTITY MANIFESTATIONS IN THE POSTMODERN LITERARY FRAME - Gasparyan, Seda; Yernjakyan, Nvard (Armenian Folia Anglistika, 2022)
National identity can be traced in almost all the spheres of human habitat – cultural, institutional, political, literary, pshychological, daily routine and many others, that is both in the verbal and non verbal activities of all and each person, respectively. In this research we look upon the British identity manifestations in the post-modern multifaceted literary frame based on the English short story contexts. Given the popular approach of the marked British conventionalism, concepts and cultural artefacts, as it were, we elucidate the stories of three contemporary women writers — A.S. Byatt; J.Gardam and D.Moggach, as a field to reveal literary reproductions of identity paradigm and its social-cultural component in view of the city of London and certain niches of its subcultures. The analysis produces challenging ideas when considering social and spatial distinctions of London’s image according to the writers’ subjective attitudes, as well as the moral of the past and present, which are portrayed by three main topics: intellectuality and erudition (the London library); arts and theatre (the National Theatre and Shakespeare); Post-colonial reality (Pakistani shopkeeper’s British dream-home), all of them as inseparable components of British national identity.